A Qualitative Exploration of the Experiences of Veterans Who Are Serving Sentences in Custody - Unwin, Michele (Journal of interpersonal violence, 2021)
The focus on veterans in research is not a novel topic; however, the majority of studies are related to trauma, employment, mental health, suicide, and substance misuse. The criminal justice system involvement with veterans is a topic that has yet to be examined to a great extent. This study, conducted with adult male prisoners, elicited information from six veterans regarding their experiences of being in the armed forces, leaving the armed forces, and becoming involved in the criminal justice system. Responses were evaluated using interpretative phenomenological analysis (IPA) and three main themes were identified: “you’re baptized into the army,” “them and us,” and “operational mind-set”; each of which comprised a number of superordinate themes. The research highlights that although it is important to acknowledge the heterogenic nature of this group, it is equally important to note that much of their thinking and behavior may be similar to those that have not had these experiences. As such, there is a need to reduce the notion that they are separate and different to other prisoners, requiring different treatment. The study highlights that many of the offending behavior programs and interventions already available to prisoners would be appropriate for this group. The current research supports the merit in creating a service in prisons that will allow ex-servicemen to meet together and access the support that is available to them. The implications of the research are discussed further.